Application of high-throughput sequencing technology in HIV drug resistance detection - Yuanyuan Zhang; Liying Ma (Elsevier, 2021)
Drug resistance via drug-resistant mutations in the human immunodeficiency virus (HIV) genome is the primary cause of antiviral therapy failure. Consequently, HIV drug resistance genotyping has become a critical approach in HIV prevention and control. Compared to the Sanger sequencing technology, high-throughput sequencing (HTS) technology has superior sensitivity and timeliness, with strong detection capabilities for low-frequency mutations. With the continued advancement of HTS technologies, their prominence in HIV drug resistance detection techniques has increased accordingly. This article will review the latest developments in HTS technology and its applications in HIV drug resistance testing.